Relationship between Socio-Economic Aspects and Education Level of Group Ages 18-25 towards Teeth-Brushing Habit (Medico Legal Update, 2021)
Background: Dental and oral health problems in the community can arise due to behavioral factors orattitudes ignoring oral and dental hygiene. The level of education and the factors that affect children’s owndental health have been presented in various studies.Objective: To analyze the relationship between socio-economic aspects and the level of education of peopleaged 18-25 years towards the habit of brushing teeth in the city of Surabaya.Method: This type of research is an observational analytic study with a design using a cross sectionalstudy approach. In this study, related data were collected regarding the relationship between education andsocioeconomic levels of the age range of 18-25 years on the habit of brushing properly taken at the sametime.Results: There was no significant relationship between education and socio-economic level with the habitof brushing teeth.Conclusion: It was concluded that there was no significant relationship between education level with thehabit of brushing teeth and the relationship of socioeconomic level with the habit of brushing teeth.